BIODIVERSITY OF BUTTERFLY SPECIES OF ORDER (LEPIDOPTERA) AND IMPACT OF CLIMATE CHANGE ACROSS DIFFERENT RURAL AREA OF GHOT, NEAR CHAMORSHI DISTRICT-GADCHIROLI (M.S.) INDIA - Deshmukh Sapana Mahesh,; Telkhade Pravin Madhukarrao,; Sapana M. Deshmukh, (The Bioscan, 2025)
All of the environmental conditions played a significant role in determining the butterfly diversity and density.They serve as excellent markers of changes in the atmosphere, climate, and seasonal ecology. Being a cold-blooded invertebrate’s butterflies are easily shows significant impact by climatic changes. Present investigation carried out for one year during October 2022 to September 2023 at rural area of Ghot, near Chamorshi District-Gadchiroli (M.S.). India. In present investigation, total 21 species were recorded and identified among these include in three families Nymphalidae belongs 14 species followed by Papilionidae with 05 species and least appearance of Pierdae with 02 species. Most of the butterfly species were very commonly called as Brush-footed butterflies followed by Papilionidae commonly called as Swallowtails species and Pierdae commonly called as white and Yellows species. As per the literature its indicate that all butterflies’species has its significant importance in balancing biodiversity, so in view of the study required future planning, climate impact and host plants conservation and also focus on the current status of biodiversity of butterflies in Ghot area near Chamorshi District-Gadchiroli (M.S.) India.